Study of inelastic processes in Li+–Ar, K+–Ar, and Na+–He collisions in the energy range 0.5–10 keV. (23rd October 2017) - Lomsadze, Ramaz A; Gochitashvili, Malkhaz R; Kezerashvili, Roman Ya; Schulz, Michael
Abstract: Absolute cross sections are measured for charge-exchange, ionization, and excitation processes within the same experimental setup for the Li + − Ar, K + − Ar, and Na + − He collisions in the ion energy range of 0.5–10 keV. The results of the measurements and schematic correlation diagrams are used to analyze and determine the mechanisms for these processes. The experimental results show that the charge-exchange processes occur with high probabilities and electrons are predominantly captured in ground states. The contributions of various partial inelastic channels to the total ionization cross section are estimated, and a primary mechanism for the process is identified. In addition, the energy-loss spectrum is applied in order to estimate the relative contribution of different inelastic channels, and to determine the mechanisms for the ionization and for some excitation processes of Ar resonance lines for the K + − Ar collision system. The excitation cross sections for the helium and for the sodium doublet lines for the Na + − He collision system both reveal some unexpected features. A mechanism to explain this observation is suggested.